Multi-Technique Approach to Enhance the Properties of Fine Recycled Aggregate Concrete - Amadi, I. G.; Beushausen, H.; Alexander, M.G. (Frontiers in Materials, 2022)
This study investigated the properties of fine recycled aggregates (FRA), with a view to enhancing their properties for structural concrete applications. The study explored several approaches including mixing; curing; systematic screening of FRA particles below 1.18 mm to reduce the adhered cement paste (ACP) content; and the use of fly ash as 30% cement replacement to modify the microstructure of FRA concrete. To test these approaches, two series of concrete mixes were prepared at 0.45 and 0.55 w/b ratio, with FRA replacing natural sand at 0, 25, and 50% by mass, and tests were carried out after 3, 28, and 180 days of curing. Results show that the combination of ACP reduction and fly ash treatment significantly enhanced the compressive strength and elastic modulus of FRA concrete, especially at 180 days, through microstructure modification and pozzolanic reactions.